Respuesta :

Answer:

[tex]f=-\frac{6g}{5}[/tex]

Step-by-step explanation:

Given: [tex]6f + 9g = 3g +f[/tex]

To solve for the value [tex]f,[/tex] we need to isolate it on one side of the equal sign. Let's move the [tex]f[/tex] on the right side to the left side by subtracting it from both sides. We then get:

[tex]5f + 9g = 3g[/tex]

Subtract [tex]9g[/tex] from both sides of the equal sign to isolate the [tex]5f.[/tex]

[tex]5f= -6g[/tex]

To solve for [tex]f,[/tex] we need to divide both sides by [tex]5[/tex] since it is being multiplied by [tex]f.[/tex]

[tex]\frac{5f}{5} =\frac{-6g}{5}\\f=-\frac{6g}{5}[/tex]